Kemampuan Berpikir Kritis Matematis Ditinjau dari Gaya Belajar dengan Metode Guided Discovery pada Siswa Kelas VIII SMP Muhammadiyah 1 Surakarta Tahun Ajaran 2016/2017 - Rahmawati, Oktaviana; , Muhammad Noor Kholid, S.Pd., M.Pd (2017)
This study aims to describe the critical thinking skill of students in terms of learning style with a category coverger, diverger, accommodator, assimilator and with the method of guided discovery. This type of research is qualitative. The subject of the research consists of four students for each learning style in class VIII-A Junior High School Muhammadiyah 1 of Surakarta. The technique of data collection on these studies is a technique now to know the learning styles of students, engineering tests to know the critical thinking ability of the students, and interviews. Prior to test students learning activities during three meetings on the material of the circle to sub the material elements of the circle, and the circumference of a circle, as well as comparison and difference between the circumference and area of a circle with the method of guided discovery. Test results and interviews are analyzed based on indicators of critical thinking that is as follows: (1) focus the question, (2) assess whether a source is reliable or not, (3) Observing and considering the report of the observation, (4) Make necessary and consider the results of the induction, and (5) Mixes. The results showed that: (1) To the indicator 1 students are able to master the accommodator, while students diverger, assimilator and converger, less able to master, (2) For indicators 2 and 4 students assimilator and converger, accommodator, less able to master, while students are less able to master the diverger, (3) to the indicator 3 students assimilator and diverger capable of controlled, while students converger and less able to master the accommodator, (4) to the indicator 5 students assimilator and converger capable of mastering While students diverger and accommodator less able to master.